Tandospirone Suppresses Impulsive Action by Possible Blockade of the 5-HT1A Receptor - Yu Ohmura; Haruko Kumamoto; Iku Tsutsui-Kimura; Masabumi Minami; Takeshi Izumi; Takayuki Yoshida; Mitsuhiro Yoshioka (Elsevier, 2013)
Higher impulsivity is observed in several psychiatric disorders and could be a risk factor for drug addiction, criminal involvement, and suicide. Although the involvement of the 5-HT1A receptor in impulsive behavior has been indicated, the effects of clinically relevant drugs have been rarely tested. In the present study, we examined whether (3aR,4S,7R,7aS)-rel-hexahydro-2-[4-[4-(2-pyrimidinyl)-1-piperazinyl]butyl]-4,7-methano-1H-isoindole-1,3(2H)-dione hydrochloride (tandospirone), an anxiolytic and a partial agonist of the 5-HT1A receptor, could affect impulsive action in the 3-choice serial reaction time task. Rats were acutely administered tandospirone (0, 0.1, and 1 mg/kg, i.p.). Tandospirone decreased the number of premature responses, an index of impulsive action, in a dose-dependent manner. N-[2-[4-(2-Methoxyphenyl)-1-piperazinyl]ethyl]-N-2-pyridinylcyclohexanecarboxamide maleate salt (WAY100635; 0.3 mg/kg, s.c.), a 5-HT1A receptor antagonist, did not reverse the suppressing effects of tandospirone on impulsive action. Moreover, a higher dose of WAY100635 (1 mg/kg, s.c.) suppressed impulsive action without tandospirone. Thus the effects of tandospirone on impulsivity might be due to the antagonistic action. Tandospirone could be a therapeutic candidate for impulsivity-related disorders. [Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.12264FP] Keywords:: impulsive behavior, inhibitory control, behavioral inhibition, anxiolytic